4D printing of mixed vegetable gel based on deformation and discoloration induced by acidification and dehydration. (25th October 2022) - Huang, Yiwen; Zhang, Min; Pattarapon, Phuhongsung; Mujumdar, Arun S.
Abstract: This research was aimed at exploring the feasibility of 4D printing of Chinese cabbage puree–carrot powder–xanthan gum mixed gel system using white vinegar and hot air dehydration (HAD) as stimuli to realize double change of shape and color. Firstly, 4D printability of five mixed vegetable gels (MVG) were characterized by water distribution and rheological properties. The results showed that apparent viscosity, G ′, G ″, G * and yield stress were positively related to carrot powder content, while transverse relaxation time ( T 2 ) were negatively related to it. Next, the formula with 15% carrot powder content was chosen as printing ink due to its better 4D printing behavior. The results showed that bending angle reached the maximum (371.01°) at 210 min, and initial green color completely turned brown at 120 min. Finally, complex models such as butterfly and four‐petal flowers were further applied to verify the feasibility of this 4D food printing. Practical Applications: This study provides a simple but innovative method for simultaneous deformation and discoloration of 3D printed objects. These procedures would allow chlorophyll‐rich vegetarian dishes show deformation and discoloration before consumption for added interest.